Soukromá korespondence jako lingvistický pramen = Private correspondence as a source of material for linguistic research work - Hladká, Zdeňka (Masarykova univerzita, 2013)
For a long time, private correspondence has been a subject of interest for scholars from the humanities, especially for historians and literary scholars, as well as for sociologists, psychologists etc. The interest in this unique kind of material is also growing in the field of linguistics. The book represents a work of several Czech scholars who have been systematically dealing with the language of correspondence, providing new approaches to this research topic. Attention is paid especially to corpus processing of private correspondence, using these sources also for the purpose of a quantitat.